Intermediate Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-894-7
ISBN 13: 978-0-13417-894-3

Chapter 1 - Mid-Chapter Check Point - Page 53: 5



Work Step by Step

$\frac{(-2^4) + (-2^2)}{-4-(2-2)}$ Remove the parentheses: $(-a) = -a$ $=\frac{(-2^4) -2^2}{-4-(2-2)}$ $=\frac{(-16) -4}{-4-(0)}$ $=\frac{-20}{-4}$ $=5$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.